Endoglin involvement in integrin-mediated cell adhesion as a putative pathogenic mechanism in hereditary hemorrhagic telangiectasia type 1 (HHT1) - Rossi, Elisa; Lopez-Novoa, José M.; Bernabeu, Carmelo (Frontiers in Genetics, 2015)
Mutations in the endoglin gene (ENG) are responsible for approximately 50% of all cases with Hereditary Hemorrhagic Telangectasia (HHT). Because of the absence of effective treatments for HHT symptoms, studies aimed at identifying novel biological functions of endoglin which could serve as therapeutic targets of the disease are needed. Endoglin is an endothelial membrane protein, whose most studied function has been its role as an auxiliary receptor in the TGF-β receptor complex. However, several lines of evidence suggest the involvement of endoglin in TGF-β-independent functions. Endoglin displays, within its zona pellucida (ZP) domain, an RGD motif, which is a prototypic sequence involved in integrin-based interactions with other proteins. Indeed, we have recently described a novel role for endothelial endoglin in leukocyte trafficking and extravasation via its interaction with leukocyte integrins. In addition, functional, as well as protein and gene expression analysis have shown that ectopic endoglin represses the synthesis of several members of the integrin family and modulates integrin-mediated cell adhesions. This review focuses on the tight link between endoglin and integrins and how the role of endothelial endoglin in integrin-dependent cell adhesion processes can provide a better understanding of the pathogenic mechanisms leading to vascular lesions in endoglin haploinsufficient HHT1 patients.